Oleocanthal, an Antioxidant Phenolic Compound in Extra Virgin Olive Oil (EVOO): A Comprehensive Systematic Review of Its Potential in Inflammation and Cancer - María González-Rodríguez; Djedjiga Ait Edjoudi; Alfonso Cordero-Barreal; Mariam Farrag; María Varela-García; Carlos Torrijos-Pulpón; Clara Ruiz-Fernández; Maurizio Capuozzo; Alessandro Ottaiano; Francisca Lago; Jesús Pino; Yousof Farrag; et al. (MDPI AG, 2023)
Background: The Mediterranean diet is linked to various health benefits, especially the consumption of olive oil as a key component. Multiple studies highlight its advantages, particularly due to its fatty acid composition and additional components like phenolic compounds. A significant antioxidant compound, oleocanthal, known for its antioxidant properties, has gained attention in the pharmaceutical industry for its anti-inflammatory and antiproliferative effects. It shows promise in addressing cardiovascular diseases, metabolic syndrome, and neuroprotection. This systematic review aims to evaluate the existing literature on oleocanthal, examining its role in biological processes and potential impact on conditions like inflammation and cancer. Methods: We performed several searches in PubMed (MEDLINE), Web of Science (WOS), and Cochrane based on the terms "Oleocanthal", "Cancer", and "Inflammation". The inclusion criteria were as follows: studies whose main topics were oleocanthal and cancer or inflammation. On the other hand, the exclusion criteria were studies that were not focused on oleocanthal, reviews, or editorial material. Given that these findings are explanatory rather than derived from clinical trials, we refrained from employing methods to assess potential bias. This systematic review did not receive any external funding. Results: We found 174 records from these searches, where we discarded reviews and editorial material, duplicated articles, and 1 retracted article. Finally, we had 53 reports assessed for eligibility that were included in this review. Discussion: OC exhibits promising therapeutic potential against both inflammation and cancer. We addressed its ability to target inflammatory genes and pathways, offering potential treatments for conditions like rheumatic diseases by regulating pathways such as NF-kB and MAPK. Additionally, OC's anticancer properties, particularly its notable inhibition of c-Met signaling across various cancers, highlight its efficacy, showcasing promise as a potential treatment.